NIR Stimulus-Responsive PdPt Bimetallic Nanoparticles for Drug Delivery and Chemo-Photothermal Therapy - Chun Chu; Zhihong Bao; Meng Sun; Xiaowei Wang; Hongyan Zhang; Weiguo Chen; Yang Sui; Ji Li; Yuanyuan Zhuang; Dongkai Wang (Pharmaceutics, 2020)
The combination of chemotherapy and phototherapy has attracted increasing attention for cancer treatment in recent years. In the current study, porous PdPt bimetallic nanoparticles (NPs) were synthesized and used as delivery carriers for the anti-cancer drug doxorubicin (DOX). DOX@PdPt NPs were modified with thiol functionalized hyaluronic acid (HA-SH) to generate DOX@PdPt@HA NPs with an average size of 105.2 ± 6.7 nm. Characterization and in vivo and in vitro assessment of anti-tumor effects of DOX@PdPt@HA NPs were further performed. The prepared DOX@PdPt@HA NPs presented a high photothermal conversion efficiency of 49.1% under the irradiation of a single 808 nm near-infrared (NIR) laser. Moreover, NIR laser irradiation-induced photothermal effect triggered the release of DOX from DOX@PdPt@HA NPs. The combined chemo-photothermal treatment of NIR-irradiated DOX@PdPt@HA NPs exerted a stronger inhibitory effect on cell viability than that of DOX or NIR-irradiated PdPt@HA NPs in mouse mammary carcinoma 4T1 cells in vitro. Further, the in vivo combination therapy, which used NIR-irradiated DOX@PdPt@HA NPs in a mouse tumor model established by subcutaneous inoculation of 4T1 cells, was demonstrated to achieve a remarkable tumor-growth inhibition in comparison with chemotherapy or photothermal therapy alone. Results of immunohistochemical staining for caspase-3 and Ki-67 indicated the increased apoptosis and decreased proliferation of tumor cells contributed to the anti-tumor effect of chemo-photothermal treatment. In addition, DOX@PdPt@HA NPs induced negligible toxicity in vivo. Hence, the developed nanoplatform demonstrates great potential for applications in photothermal therapy, drug delivery and controlled release.